Black spruce seed availability and viability after fire, Northwest Territories, Canada - Reid, Kirsten A.; Day, Nicola J.; Alfaro Sánchez, Raquel; Johnstone, Jill F.; Cumming, Steven G.; Mack, Michelle C.; Turetsky, Merritt R.; Walker, Xanthe J.; Baltzer, Jennifer L. (Zenodo, 2023)
Context : Black spruce ( Picea mariana ) is an important conifer in boreal North American that develops a semi-serotinous, aerial seedbank and releases a pulse of seeds after fire. Variation in post-fire seed rain has important consequences for black spruce regeneration and stand composition. Aims : We explore the possible effects of changes in fire regime on the abundance and viability of black spruce seeds following a very large wildfire season in the Northwest Territories, Canada (NWT). Methods: We measured post-fire seed rain over two years at 25 black sprucedominated sites and evaluated drivers of stand characteristics and environmental conditions on total black spruce seed rain and viability. Results : We found a positive relationship between black spruce basal area and total seed rain. However, at high basal areas this increasing rate of seed rain was not maintained. Viable seed rain was greater in stands that were older, closer to unburned edges, and where canopy combustion was less severe. Finally, we demonstrated positive relationships between seed rain and seedling establishment, confirming our measures of seed rain were key drivers of post-fire forest regeneration. Conclusion: These results suggest that black spruce recruitment after fire may be reduced with projected increases in fire activity. This dataset can be opened in excel. Funding provided by: Government of the Northwest Territories* Crossref Funder Registry ID: Award Number: Project 170 Funding provided by: Natural Sciences and Engineering Research Council of Canada Crossref Funder Registry ID: http://dx.doi.org/10.13039/501100000038 Award Number: Funding provided by: Northern Scientific Training Program* Crossref Funder Registry ID: Award Number: Funding provided by: NSF DEB RAPID* Crossref Funder Registry ID: Award Number: 1542150 Funding provided by: NASA Arctic Boreal and Vulnerability Experiment (ABoVE)* Crossref Funder Registry ID: Award Number: Legacy Carbon grant: NNX15AT71A Funding provided by: CFREF Global Water Futures* ...